Idiopathic Nonsurgical Pneumoperitoneum in Healthy Individuals after Endoscopy: Coincidence or Consequence? - Jong Soo Lee; Dong-Hoon Yang; Eun Hee Kim; Jin Hwa Park; Sungwon Park; Hye Won Park (Case Reports in Gastrointestinal Medicine)
Idiopathic pneumoperitoneum has an unknown etiology despite exploratory laparotomy. However, it may occur without definite abdominal symptoms; thus, adequate management could be in clinical dilemma. We experienced three cases of idiopathic nonsurgical pneumoperitoneum in healthy individuals during a health check-up. Their cases were not accompanied by any relevant etiology or definite abdominal symptoms. All of the three cases exhibited a benign clinical course. The three patients underwent an abdominal computed tomography (CT) scan as part of a health check-up program, which incidentally revealed free air in the right paracolic gutter without evidence of visceral perforation or inflammation. Among the three cases, two patients underwent colonoscopy before abdominal CT, whereas one patient did not. Two cases were completely asymptomatic and were observed without any treatment in the outpatient clinic. Only the third case with minimal symptoms was treated conservatively for a short time. If a small amount of free air typically located in the right paracolic gutter is detected in the absence of perforation during colonoscopy, close observation without unnecessary treatment would be sufficient.